Efficacy and safety of a biomarker-driven cetuximab-based treatment regimen over 3 treatment lines in mCRC patients with RAS/BRAF wild type tumors at start of first line: The CAPRI 2 GOIM trial - Martini, Giulia; Ciardiello, Davide; Napolitano, Stefania; Martinelli, Erika; Troiani, Teresa; Latiano, Tiziana Pia; Avallone, Antonio; Normanno, Nicola; Di Maio, Massimo; Maiello, Evaristo; Ciardiello, Fortunato (Frontiers in Oncology, 2023)
Background: Monoclonal antibodies targeting EGFR such as cetuximab or panitumumab represent a major step forward in the treatment of RAS wild type (WT) metastatic colorectal cancer (mCRC). Unfortunately, mechanisms of primary and acquired resistance limit their use, with a huge percentage of patients succumbing to the disease. In the last years, several molecular biomarkers have been proposed as potential predictors of resistance to anti-EGFR agents. Among these, RAS mutational status is today the only molecular marker to negatively select mCRC patients to anti-EGFR-based treatment. Liquid biopsy analysis allows to a dynamic and longitudinal assessment of mutational status during mCRC disease and has provided important information on the use of anti-EGFR drugs beyond progression or as rechallenge strategy in patients with RAS WT tumors. Methods: The phase II CAPRI 2 GOIM trial investigates the efficacy and safety of a bio-marker-driven cetuximab-based treatment regimen over 3 treatment lines in mCRC patients with RAS/BRAF WT tumors at start of first line. Discussion: the aim of the study is to identify patients with RAS/BRAF WT tumors that are “addicted” to an-anti EGFR based treatment along three lines of therapy. Moreover, the trial will evaluate the activity and efficacy of cetuximab re-introduction in combination with irinotecan as 3rd line therapy as rechallenge for those patients that will be treated in second line with FOLFOX plus bevacizumab, having a RAS/BRAF mutant disease at progression after FOLFIRI plus cetuximab first line. A novel characteristic of this program is that the therapeutic algorithm will be defined at each treatment decision (first line, second line and third line) in a prospective fashion in each patient by a liquid biopsy assessment of RAS/BRAF status by a comprehensive 324 genes Foundation One Liquid assay (Foundation/Roche). Trial registration: EudraCT Number: 2020-003008-15, Clinicaltrial.gov identifier: NCT05312398